Ancient and High Crosses of Cornwall : Cornwall's Earliest, Tallest and Finest Medieval Stone Crosses /: Cornwall's Earliest, Tallest and Finest Medieval Stone Crosses. (2021) - Preston-Jones, Ann; Langdon, Andrew; Okasha, Elisabeth
No abstract available